A systematic review on the trend of transcriptomic study in livestock: An effort to unwind the complexity of adaptation in a climate change environment - Putri Kusuma Astuti; Péter Sárkány; George Wanjala; Zoltán Bagi; Szilvia Kusza (Heliyon)
Heat stress has been proven to cause negative effects on livestock leading to lower productivity and economic value. Understanding how heat stress manifests within an animal's body is the first step in devising a heat stress mitigation strategy; transcriptomic studies are one of the methods used. Here, using a systematic literature review methodology, we examine the recent decade of transcriptomics' application to the study of livestock adaptation. We identified 152 studies that met our criteria for using transcriptome methods to heat stress adaptation and were published within the last ten years. Our analysis demonstrates the growing popularity and application of transcriptome approaches in the investigation of the response of ruminants, pigs, and poultry livestock to heat stress. Majority of the works was done in chicken and cattle using multiple organs as the sample, with qRT-PCR as the most employed technique. It has been established that a variety of biomarkers can be used to assess animals under heat stress, such as the HSPs, ILs, and TLRs. Although transcriptomics has lately been employed extensively to uncover the mechanism of heat adaptation, this adaptive feature's complex mechanism remains unclear, leaving many knowledge gaps for investigation. A more complex studies involving more various cell types, organs, or even model organisms using multi-omics approach could be the future research direction in understanding the heat stress effects on livestock better.